2021
DOI: 10.9734/jpri/2021/v33i28b31532
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors during Pregnancy for Asymptomatic Bacteriuria

Abstract: Introduction: Asymptomatic bacteriuria in pregnancy (ABU) is poorly understood and neglected in developing countries. It causes certain lethal maternal and fetal consequences if left untreated including low weighted births, premature delivery, full-blown urinary tract infection and pyelonephritis. Objective: Our aim was to explore such factors having bad impact on pregnancy associated with asymptomatic bacteriuria and aware our community about these unspoken perils so that ABU likelihood may be reduced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Mahmoud and his colleagues reported that the incidence of UTIs in pregnant women was the highest in the multigravidas [25]. It was reported that gravidity was a strong risk factor associated with ASB where 55 (73.3 %) were third gravida or more [26]. Similarly, Tadesse and his team demonstrated that ASB was substantially correlated with women's age, wages, and gestational time [21], while Bahavana and his colleagues observed that 71.8% of the ASB cases were recorded within the third trimester [27].…”
Section: Discussionmentioning
confidence: 99%
“…Mahmoud and his colleagues reported that the incidence of UTIs in pregnant women was the highest in the multigravidas [25]. It was reported that gravidity was a strong risk factor associated with ASB where 55 (73.3 %) were third gravida or more [26]. Similarly, Tadesse and his team demonstrated that ASB was substantially correlated with women's age, wages, and gestational time [21], while Bahavana and his colleagues observed that 71.8% of the ASB cases were recorded within the third trimester [27].…”
Section: Discussionmentioning
confidence: 99%
“…Prokaryotic urinary tract infections are a strong inflictor for approximately more than 150 million population per year, among them a huge number of sufferers are females during pregnancy which could be symptomatic or asymptomatic [1]. Anatomical and Physiological alteration during pregnancy enhances the potentiality for easy bacterial contamination, colonization, and proliferation of microorganisms in the urinary tract [2,3].…”
Section: Introductionmentioning
confidence: 99%